Aptamer‐Mediated Protein Molecular Recognition Driving a DNA Tweezer Nanomachine. Issue 1 (20th December 2016) - Shiu, Simon Chi‐Chin; Cheung, Yee‐Wai; Dirkzwager, Roderick M.; Liang, Shaolin; Kinghorn, Andrew B.; Fraser, Lewis A.; Tang, Marco S. L.; Tanner, Julian A.
Abstract : Nucleic acid‐mediated nanomachines have significant potential in biomedical applications but new approaches that link molecular recognition of proteins to change in nucleic acid structure and function are required. Here, a split DNA aptamer is integrated into G‐quadruplex tweezers, which close in the presence of the malaria biomarker protein Plasmodium falciparum lactate dehydrogenase (PfLDH). Closing of the tweezers enables G‐quadruplex hemin mediated peroxidase activity, which can be observed colorimetrically. The PfLDH aptamer is split within an asymmetric internal loop and incorporated into the tweezers maintaining aptamer binding capability. Spacing between the G‐quadruplex structure and split aptamer, together with extent of complementarity, is found to be critical for optimization to enhance catalytic performance. The integrated split aptamer is observed to maintain the high specificity to Plasmodium falciparum lactate dehydrogenase of the parent aptamer. Split aptamer approaches have significant potential to functionalize nucleic acid nanostructures for protein molecular recognition. Abstract : It is demonstrated how aptamer‐mediated protein recognition can drive a DNA tweezer nanomachine. Plasmodium falciparum lactate dehydrogenase closes the tweezers leading to G‐quadruplex formation thereby enhancing hemin mediated peroxidase activity.